VD_FINDINFO AVS 52/20 - 29/2021 vom 21. Juni 2021 - VD Tribunal cantonal (2021)
ALLOCATION POUR IMPOTENT, ACTE ORDINAIRE DE LA VIE, MANGER, IMPOTENCE MOYENNE | 43bis LAVS, 17 al. 2 LPGA, 9 LPGA, 37 RAI